The Effect of Market Orientation and Product Creativity on Competitive Advantage at Etsuko Kitchen Tomohon - Meisie Tulung; Stefani Angmalisang (AIBPM Publisher, 2022)
This study aimed to find out the effect of market orientation and product creativity on the competitive advantage at Etsuko Kitchen Tomohon. The population was the customer of Etsuko Kitchen Tomohon. The number of samples was calculated based on Lemeshow formula that was as many as 100 respondents. Data collection was conducted using questionnaire. Data analysis that used in this study was t-test, F-test and multiple linear regressions processed using SPSS program, version 2022. The results showed that market orientation variable in t-test had tcount value of 5.026 > ttable value of 1.984 and has significant value of 0.000 < 0.05, and product creativity variable had tcount 10.384 > ttable 1.984 and the significant score of 0.000 < 0.05. The research results showed that market orientation variable and the product creativity partially and simultaneously had positive and significant effect on the competitive advantage. Thus, it could be concluded that the role of market orientation and product creativity on the competitive advantage was 74.4% and the remaining, i.e., 25.6%, was influenced by the other variables which were not included in this study. Keywords: Competitive Advantage, Market Orientation, Product Creativity.